Assessment of Cultural-Historical and other Ecosystem Values of Djerdap National Park - Dobričić, Milica; Sekulić, Goran; Josimović, Boško D (Arhitektura i urbanizam, 2021)
This paper points out the importance of assessing the cultural-historical and other ecosystem values ​​of protected areas, on the example of applying protected areas benefit assessment tool (PA-BAT). This method has so far been applied in seven Dinaric Arc countries (Slovenia, Croatia, Bosnia and Herzegovina, Montenegro, North Macedonia, Albania and Serbia) in south-eastern Europe, as well as other countries of the world (Colombia, Turkey, Myanmar, USA and Ethiopia), with the aim of helping to gather information on the values ​​and benefits of individual protected areas in relation to ecosystem services, using a participatory approach. On the example of the Djerdap National Park (in the Republic of Serbia), the results of the application of the PA-BAT method are given, that is, the results of the assessment of 22 ecosystem values with special reference to cultural and historical values as one of the ecosystem services of this protected area, as well as the results of previously conducted assessments of the ecosystem values of this area. The aim of this paper is to contribute to a better understanding and promotion of the application of the concept of ecosystem services in the preservation of cultural-historical and other ecosystem values by applying PA-BAT evaluation methods.